-6z+13=7z-5

Simple and best practice solution for -6z+13=7z-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6z+13=7z-5 equation:


Simplifying
-6z + 13 = 7z + -5

Reorder the terms:
13 + -6z = 7z + -5

Reorder the terms:
13 + -6z = -5 + 7z

Solving
13 + -6z = -5 + 7z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-7z' to each side of the equation.
13 + -6z + -7z = -5 + 7z + -7z

Combine like terms: -6z + -7z = -13z
13 + -13z = -5 + 7z + -7z

Combine like terms: 7z + -7z = 0
13 + -13z = -5 + 0
13 + -13z = -5

Add '-13' to each side of the equation.
13 + -13 + -13z = -5 + -13

Combine like terms: 13 + -13 = 0
0 + -13z = -5 + -13
-13z = -5 + -13

Combine like terms: -5 + -13 = -18
-13z = -18

Divide each side by '-13'.
z = 1.384615385

Simplifying
z = 1.384615385

See similar equations:

| 8(x+1)=5(x+1) | | 0.25x-2=8 | | 4y^4=32y^3-68y^2 | | 9n-7=5a+5 | | sin(8x)=sin(10x) | | 25x^2-10xy+12y=0 | | 0=1x+10 | | 3(s+4(s+12))= | | 28x^2+28x+7=0 | | 6x-28y=-10 | | 4.2y-2y=16.8 | | 6x-28=-10 | | 2(-2-2m)=-4-3m | | 7-3(4x+2)=6(2x+3)17 | | X+2=2(3x-8) | | 14+19+x*3=17 | | 4a^3+6a^2+5a=0 | | 1+x=10-2x | | -6x-15=58 | | ax+b+cx=d | | 2x^2-4=60 | | x^2+2x(0.4)=0.84 | | -x+2y+4z=-11 | | f(x)=x^2+13x+37 | | B=pn+pforn | | 12x+2=(7)2x-3 | | 6p^2+25x+4=0 | | y=.33(x-27) | | 2.75f=24.5 | | 5-6lnx=20 | | (3x-c)(x-3)=12 | | 5n^2=-5n+160 |

Equations solver categories